MAPT-A152T mutation drives neuronal hyperactivity through Fyn-NMDAR signaling in human iPSC-Derived neurons: Insights into Alzheimer's pathogenesis - Maika Itsuno; Hirokazu Tanabe; Etsuko Sano; Takashi Sasaki; Chisato Oyama; Hiroko Bannai; Koichi Saito; Kazuhiko Nakata; Setsu Endoh-Yamagami; Hideyuki Okano; Sumihiro Maeda (Regenerative Therapy)
Introduction: Tau protein plays a pivotal role in the pathogenesis of Alzheimer's disease (AD) and in regulating neuronal excitability. Among tau-coding microtubule associated protein tau (MAPT) gene mutations, the A152T mutation is reported to increase the risk of AD and neuronal excitability in mouse models. Methods: To investigate the effects of MAPT gene expression and its mutations on neuronal activity in human neurons, we employed genome editing technology to introduce the A152T or P301S mutations into induced pluripotent stem cells (iPSCs). We then differentiated them into excitatory and inhibitory neurons. As a control, iPSCs in which the MAPT gene was replaced with a fluorescent protein were also created. Results: In excitatory neuronal cultures, the A152T mutation was found to enhance spontaneous neuronal activity and the association of tau and Fyn. However, in inhibitory neuron-enriched cultures, the A152T mutation did not affect neuronal activity. Inhibition of NMDA receptors (NMDAR) and the reduction of tau protein levels decreased neuronal excitability in both A152T/A152T and healthy control (WT/WT) excitatory neurons. In addition, the A152T mutation increased the interaction between tau and Fyn. These findings suggest that the tau-Fyn interaction plays a critical role in regulating neuronal activity under physiological conditions, while the A152T mutation enhances neuronal activity by strengthening this endogenous interaction between tau and Fyn. In addition, transcriptomic analysis revealed structural changes specific to excitatory neurons with the A152T mutation. Common changes observed in both A152T and P301S lines recapitulated a dedifferentiation phenotype, consistent with previous reports. Conclusions: These data demonstrate that the A152T mutation in the MAPT gene increases neuronal excitability through the tau-Fyn-NMDAR pathway in excitatory neurons, shedding light on its role in AD pathogenesis.